Self-Efficacy On The Learning Independence Of Class Xii Students Of Culinary Smk Negeri 9 Padang - Andriyani, Monica; Gusnita, Wiwik; Kasmita, Kasmita; Andriani, Cici (Universitas Negeri Padang, 2025)
This research is based on the low learning independence of students as seen from learning initiatives and responsibilities and students do not have self-efficacy as seen from self-confidence, attitude and persistence in completing tasks. This study aims to describe students' self-efficacy, describe learning independence, and analyze the influence of self-efficacy on the learning independence of grade XII students of Culinary SMK Negeri 9 Padang. This type of research is quantitative with a regression approach, The population in this study is grade XII students majoring in Culinary at SMK Negeri 9 Padang as many as 224 students. The research sample was 144 students with random sampling technique. Data collection was carried out by distributing questionnaires directly using a likert scale that has been tested for validity and reliability. The data were analyzed using descriptive analysis. The results of the study showed that the self-efficacy of students in grade XII Culinary as a whole was in the medium category with a percentage of 40%, and the learning independence of students was in the medium category with a percentage of 35%. The results of the hypothesis test can be concluded that there is a positive and significant relationship between self-efficacy and learning independence of grade XII Culinary students at SMK Negeri 9 Padang.